Matrine in cancer therapy: antitumor mechanisms and nano-delivery strategies - Meng, Dandan; Cui, Zhenhua; Li, Lexin; Shang, Qingxin; Chen, Xiqi (Frontiers in Pharmacology, 2025)
Cancer remains one of the leading causes of death worldwide. The severe adverse reactions and toxic side effects associated with conventional treatments such as surgery, radiotherapy, and chemotherapy pose significant challenges for researchers and clinical practitioners. These limitations have driven the pursuit of more advanced and effective therapeutic approaches. In recent years, natural products have attracted considerable attention in the field of disease treatment and have become an important source for new drug development. Matrine, a major active component of the traditional medicinal plant Sophora flavescens, exhibits a broad range of pharmacological activities, particularly notable antitumor effects. Its antitumor mechanisms include the induction of apoptosis, autophagy, and ferroptosis in tumor cells, as well as the inhibition of tumor cell proliferation, migration, and invasion. With the continuous advancement of therapeutic technologies and the emergence of novel drug delivery strategies, the integration of natural products into cancer therapy has gained renewed significance in the context of innovative delivery systems. Based on this, the present review comprehensively discusses and analyzes the antitumor mechanisms of matrine and its application in nano-delivery systems, highlighting their progress and potential in major disease intervention strategies. This provides new insights for the development and application of advanced drug delivery strategies and technologies in both basic and clinical pharmaceutical research.